2022
DOI: 10.1155/2022/2577222
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination and Occurrence of Aflatoxins in Processed Baobab Products in Kenya

Abstract: Baobab fruit demand has been on the rise in the recent past, and in an attempt to match the demand, farmers and middlemen are forced to harvest immature fruits which are not fully dried. To ensure an acceptable moisture content, baobab fruits are subjected to solar drying, which is a slow process and often carried out in open and unhygienic conditions raising safety concerns. This study was conducted to investigate the microbial and aflatoxin contamination levels in ready-to-eat baobab products from selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This quality predicts that freeze-dried and hot air-dried quail eggs will have a long shelf life as opposed to pasteurized and liquid quail eggs with a short shelf life. In a study of the quality of solar-dried baobab fruits in Kenya, James et al [ 15 ] found that the water activity of baobab pulp from formal processors ranged from 0.53 to 0.74 while that from informal processors ranged from 0.53 to 0.75.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This quality predicts that freeze-dried and hot air-dried quail eggs will have a long shelf life as opposed to pasteurized and liquid quail eggs with a short shelf life. In a study of the quality of solar-dried baobab fruits in Kenya, James et al [ 15 ] found that the water activity of baobab pulp from formal processors ranged from 0.53 to 0.74 while that from informal processors ranged from 0.53 to 0.75.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the dry matter values of these egg products comply with the EECUN [ 9 ] standard which requires a minimum dry matter of 22% for liquid eggs and 95% for dried eggs. James et al [ 15 ] showed that the dry matter contents of dried baobab pulp from formal processors ranged from 92.27% to 84.94% compared to 89.50% to 76.53% for informal processors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, AF contamination due to A. parasiticus and A. flavus L. was identified in the baobab fruit in Kenya. The toxin concentration was due to poor postharvesting practices (James et al., 2022). Certainly, dry fruits like dates, pistachios, and walnuts are more prone to AFB1, AFB2, AFG1, and AFG2 contamination at all stages, from harvest to marketing.…”
Section: Mycotoxins In Fruit and Fruit Productsmentioning
confidence: 99%